The Impact of Supply Chain Capabilities on Logistic Efficiency for the Construction Projects - Muhammad Saeed Shahbaz; Muhammad Afzal Soomro; Nadeem Ul Kareem Bhatti; Zuhairuddin Soomroe; Mir Zafarullah Jamali (Civil Engineering Journal, 2019)
Rapid technological advancements force organizations to be more proactive and efficient it operations while previous studies revealed that most of the public sector projects go over in term of time and cost. Although extensive literature is available but only for the private sector, the investigations on the public sector are scarce. After plentiful literature, it has found that timely and sage supply chain is a major hurdle. Various strategies and approaches have been proposed to tackle the situation but after a thorough investigation, it was found that flexibility and collaboration are the topmost influencing factors in improving logistic efficiency. Thus the aim of this study is to empirically verify the positive impact of flexibility and collaboration on logistic efficiency. A questionnaire was adopted and distributed by random sampling to the strategic level of the construction projects in the city of Lahore, Pakistan. Multiple regressions were applied through SPSS. The finding of the study revealed that flexibility contributes 33%, collaboration contributes 35.5% in the logistic efficiency. It can be concluded that construction projects must be flexible and force stakeholders for collaboration. This study added in the frame of knowledge as new findings for public sector projects. This study will help the managers in completing their projects timely and accurately.